Active bait-fishing by Ardea alba (Pelecaniformes: Ardeidae) in Argentina (UNED Research Journal, 2018)
The behavior of active bait fishing has been recorded in species of the family Ardeidae. For the Great Egret (Ardea alba) there is only one previous record in the literature. By this contribution, a new record of active bait fishing in a Urban Park by the Great Egret is reported.
Keywords: Ardeidae; tool-use; Argentina; feeding